Dendritic cells subsets mediated immune response during Plasmodium berghei ANKA and Plasmodium yoelii infection. Issue 2 (June 2015) - Keswani, Tarun; Sengupta, Anirban; Sarkar, Samrat; Bhattacharyya, Arindam
Graphical abstract: Highlights: PbA -infected mice developed a greater number of myeloid and mature DCs. Plasmodium yoelii infected mice displayed more plasmacytoid DC and immature DCs. PbA infection shows higher level of Cd11c + IL-12 +, whereas reduced Cd11c + IL-10 + . Differential expression of FoxP3, IL-17, TGF-β and IL-6 during malaria infection. Splenic DCs are responsible for the irregularity in the host pathogenesis. Abstract: The roles of dendritic cells (DCs) in mediating immunity against Plasmodium infection have been extensively investigated, but immune response during pathogenesis of malaria is still poorly understood. In the present study, we compared the splenic DCs phenotype and function during P . berghei ANKA ( PbA ) or P . yoelii ( P . yoelii ) infection in Swiss mice. We observed that PbA -infected mice developed more myeloid and mature DCs capable of secreting IL-12, while P . yoelii -infected mice had more plasmacytoid and immature DCs secreting higher levels of IL-10. Expression of FoxP3, IL-17, TGF-β and IL-6 were also different between these two infections. Thus, these results suggest that the phenotypic and functional subsets of splenic DCs are key factors for regulating immune responses to PbA and P . yoelii infections.